Selected metabolic aspects of elastin and collagen fiber proteolysis in diseases of the respiratory system – the significance of α1 antitrypsin deficiency - Dżeljilji, Agata; Rokicki, Wojciech; Karuś, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The process of elastin and collagen fiber destruction was presented based on the example of the changes taking place in the course of chronic obstructive pulmonary disease and primary spontaneous pneumothorax. In 1963, when analyzing patients with α1 antitrypsin deficiency, Dr Laurell and Dr Eriksson hypothesized that elastolysis plays a role in the pathogenesis of emphysema, which marked the beginning of studies aimed at analyzing this process. The present work concerns new scientific reports regarding the hypothesis. The most important risk factors include protease-antiprotease imbalance and α1 antitrypsin protein deficiency.